Shanzhai et culture du faire en Chine - Julia Nawrocki (EchoGéo)
This work investigates how digital cultures produce geographic space and how this one influences back technological innovation. It shows how Shenzhen’s maker movement has developed in an inherited manufacturing region, echoing local shanzhai culture. This movement permitted to conceptualize a new open innovation model inspired from open-source ideology, which fuels the effervescence of a maker’s scene, thus producing new spatial and productive dynamics.